Interleukin 6 as a key inflammatory predictor of gestational diabetes – clinical and biochemical evidence - Hadi, Sadiq Hassan; Hassan, Abdul-Samad Uleiwi; Abdalredha, Redha Dawud (European Journal of Clinical and Experimental Medicine, 2025)
Introduction and aim. Gestational diabetes mellitus (GDM) is a prevalent metabolic disorder in pregnancy associated with significant maternal and fetal complications. Chronic low-grade inflammation is increasingly recognized as a key contributor to GDM pathophysiology, with interleukin 6 (IL-6) emerging as an important mediator of insulin resistance. The aim was to investigate the relationship between IL-6 levels and metabolic parameters in pregnant women with and without GDM, and to evaluate the diagnostic performance of IL-6 for distinguishing GDM. Material and methods. A total of 45 pregnant women with GDM and 45 normoglycemic controls between 24 and 28 weeks of gestation were enrolled. Clinical data age, body mass index (BMI), gestational age, fasting insulin, oral glucose tolerance test (OGTT), and lipid profile were assessed. IL-6 was quantified by high-sensitivity enzyme-linked immunosorbent assay. Correlation analysis, multiple linear regression, and receiver operating characteristic (ROC) curve analysis were performed using SPSS. Results. Women with GDM exhibited significantly higher IL-6 levels (25.35±11.76 ng/L) than controls (11.02±3.59 ng/L, p<0.001). IL-6 showed strong positive correlations with fasting insulin (r=0.900, p<0.001) and OGTT (r=0.684, p<0.001). Multiple regression indicated that gestational age, BMI, and total cholesterol were significant predictors of IL-6 in GDM (p<0.05). ROC analysis revealed an area under the curve of 0.923 (p<0.001) for IL-6, with a sensitivity of 88.9% and specificity of 78.3% at the cutoff of 13.243 ng/L. Conclusion. Elevated IL-6 is strongly associated with insulin resistance and dyslipidemia in GDM, suggesting a potential role as an inflammatory biomarker for early risk stratification. Incorporating IL-6 measurement into GDM screening protocols may enhance diagnostic accuracy and facilitate timely interventions to improve pregnancy outcomes.